Unraveling the unique butyrate re-assimilation mechanism of Clostridium sp. strain WK and the application of butanol production from red seaweed Gelidium amansii through a distinct acidolytic pretreatment. (December 2021) - Zhang, Kan; Hong, Ying; Chen, Chaoyang; Wu, Yi-Rui
Graphical abstract: Highlights: Clostridium sp. strain WK demonstrates a strong tolerance of butyrate up to 30 g/L. The butanol production was enhanced to be 13.96 g/L by adding 24 g/L butyrate. Genes buk and ptb were more crucial than ctfAB for the butyrate re-assimilation. An improved yield of butanol from Gelidium amansii was established by 29.9 folds. Abstract: Exploration of the algae-derived biobutanol synthesis has become one of the hotspots due to its highly cost-effective and environment-friendly features. In this study, a solventogenic strain Clostridium sp. strain WK produced 13.96 g/L butanol with a maximal yield of 0.41 g/g from glucose in the presence of 24 g/L butyrate. Transcriptional analysis indicated that the acid re-assimilation of this strain was predominantly regulated by genes buk - ptb rather than ctfAB, explaining its special phenotypes including high butyrate tolerance and the pH-independent fermentation. In addition, a butyric acid-mediated hydrolytic system was established for the first time to release a maximal yield of 0.35 g/g reducing sugars from the red algal biomass ( Gelidium amansii ). Moreover, 4.48 g/L of butanol was finally achieved with a significant enhancement by 29.9 folds. This work reveals an unconventional metabolic pathway for butanol synthesis in strain WK, and demonstrates the feasibility to develop renewable biofuels from marine resources.